THE IMPACT OF GREEN TEA ON BLOOD FLUIDITY IMPROVEMENT AND WEIGHT LOSS - Djoko Agus Purwanto; Asri Darmawati; purwaningsih purwaningsih (Universitas Airlangga, 2017)
Introduction: Various studies have shown the benefi cial effects of green tea, not only on cardiovascular diseases but also on type 2 diabetes. Method: In this study, the preparation of green tea water extract has been standardized to (-)- epigalocatechin gallate (EGCG), the major component of green tea. The role of green tea water extract on blood fl uidity and diabetes diseases has been studied in 13 Fructose-Fed Rat (FFR). The rats were given high fructose diet ad libitum for one week and then combination with green tea water extract every day for 6 days. Results: The results show, green tea water extract can reduces 100 μL blood passage times of wistar rat signifi cantly (p<0.01) by Micro-Channel Array Flow Analyzer (MC-FAN) instrument. Green tea water extract also had strong effect in reducing abdominal fat (p<0.05), blood glucose level (p<0.01) and body weight (p<0.01). Discussion: These results suggest that green tea water extract may has benefi cial effects for the treatment of diabetes and reduce blood viscosity. Keywords: green tea, (-)-epigallocatechin gallate, HPLC, blood fl uidity, fructose-fed rat